Pemanfaatan Inovasi Teknologi untuk Pemberdayaan Komunitas dalam Penanganan Epilepsi yang Berkelanjutan : Review Article - Lestari, Nova Dian; Fitriani, Dewi (JKA, 2025)
Challenges in managing epilepsy arise not only from clinical aspects, but also from social stigma, limited access to diagnostic and therapeutic services, and the general public's lack of understanding. This article explores how technological advancements can be utilized to empower communities in raising awareness and achieving sustainable epilepsy management. Through a descriptive and analytical approach based on global data and field experience, this study discusses various innovations such as digital applications, wearable devices, telemedicine services, e-learning platforms, and Virtual Reality-based therapy. Evidence shows that the use of technology can significantly expand access to healthcare services, enhance the competencies of medical personnel, and reduce stigma. It is concluded that synergy among stakeholders and the contextual adaptation of technology within communities are key strategies for improving the quality of epilepsy care